2023
DOI: 10.3390/brainsci13050751
|View full text |Cite
|
Sign up to set email alerts
|

Motor-Related Mu/Beta Rhythm in Older Adults: A Comprehensive Review

Abstract: Mu rhythm, also known as the mu wave, occurs on sensorimotor cortex activity at rest, and the frequency range is defined as 8–13Hz, the same frequency as the alpha band. Mu rhythm is a cortical oscillation that can be recorded from the scalp over the primary sensorimotor cortex by electroencephalogram (EEG) and magnetoencephalography (MEG). The subjects of previous mu/beta rhythm studies ranged widely from infants to young and older adults. Furthermore, these subjects were not only healthy people but also pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…Moreover, another publication found that beta coherence in the unlesioned hemisphere had a negative correlation with FMA-UL ( Simis et al, 2016 ). We highlight that, from the variables tested, only age was a confounder in the model, which may be explained by structural and functionally changes related to aging, what is reflected in neurophysiological measures ( Inamoto et al, 2023 ). Also, the lack of significance of the variables tested as confounders may be related to the limitation of statistical power.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, another publication found that beta coherence in the unlesioned hemisphere had a negative correlation with FMA-UL ( Simis et al, 2016 ). We highlight that, from the variables tested, only age was a confounder in the model, which may be explained by structural and functionally changes related to aging, what is reflected in neurophysiological measures ( Inamoto et al, 2023 ). Also, the lack of significance of the variables tested as confounders may be related to the limitation of statistical power.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, the observation of increased power in the Somatomotor network matches previous whole-brain analysis indicating motor regions as those with higher differences in beta power between young and older cohorts (Heinrichs-Graham and Wilson, 2016). Changes in beta power at rest are thought to index age-related changes in GABAergic inhibition (Inamoto et al, 2023; Rossiter et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the beta band has been found to be involved in emotion and long-term memory tasks [64]. However, the beta frequency band is mainly considered the default rhythm of the sensorimotor system, tightly associated with motor processes [65][66][67]. Beta oscillations are found in almost all structures involved in motor processes, including muscles, dorsal and basal ganglia, and cortex.…”
Section: Discussionmentioning
confidence: 99%